2023
DOI: 10.1101/2023.11.29.569233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The balance between ATR and DDK activities controls TopBP1-mediated locking of dormant origins at the pre-IC stage

Stéphane Koundrioukoff,
Su-Jung Kim,
Nathan Alary
et al.

Abstract: SummaryReplication stress, a major hallmark of cancers, and ensuing genome instability source from impaired progression of replication forks. The first line of defense against fork slowing is compensation, a long-described process that elicits firing of otherwise dormant origins. It remains unclear whether compensation requires activation of the DNA replication checkpoint or passively results from lengthening of the window of time during which dormant origins can fire when fork progression slows, or both. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…It is, therefore, tempting to speculate that in the absence of Plk1, the recycling of Treslin/MTBP and TopBP1 towards neighboring origins is slowed down, resulting in a decrease in the initiation rate. In further support of this hypothesis, a recent study showed that for dormant origin firing, the linear correlation between IODs and fork speed at different concentrations of aphidicolin is also dependent on TopBP1 but not on Chk1 [67]. Another possibility is that Plk1 directly interacts with replication fork proteins to reduce fork speed.…”
Section: Discussionmentioning
confidence: 90%
“…It is, therefore, tempting to speculate that in the absence of Plk1, the recycling of Treslin/MTBP and TopBP1 towards neighboring origins is slowed down, resulting in a decrease in the initiation rate. In further support of this hypothesis, a recent study showed that for dormant origin firing, the linear correlation between IODs and fork speed at different concentrations of aphidicolin is also dependent on TopBP1 but not on Chk1 [67]. Another possibility is that Plk1 directly interacts with replication fork proteins to reduce fork speed.…”
Section: Discussionmentioning
confidence: 90%